광학 전산화단층촬영 스캐너 사용을 위한 중합체 겔과 BANG TM 겔 선량계의 특성 비교 - 장경환; Kyung Hwan Chang (방사선기술과학, 2023)
The purpose of this study was to compare the basic radiological characteristics of in-house polymer gel and commercially-available gel (BANGTM) gel dosimeters with a spectro-photometer to use a optical computed tomography (CT) scanner. We investigated the radiological characteristics including dose linearity, absorbance spectrum, dose rate dependency and inter-and intra-reproducibility at wavelengths of 590, 600 and 630 nm. The optimal dose linearities of two gel dosimeters showed R2 value of 0.939 and 0.948 at wavelengths of 590 nm and 600 nm, respectively. For two polymer gel dosimeters, there is no peak sensitivity within the range of all wavelengths in absorbance spectrum. For in-house gel dosimeter, the dose rate dependency were within 5% for all wavelengths except for the dose rate of 100 MU/min. For BANGTM gel dosimeter, the dose rate dependency showed an error range of ±5% for all wavelengths. The inter-and intra-reproducibility of two gel dosimeters were within the range of 2.5%. We have confirmed that the two gel dosimeters was appropriate for use with a optical CT scanner.